The Use of ICT For Poverty Alleviation In Gubugklakah Village, Malang Regency - Rachmad Gustomy; Ratnaningsih Damayanti; Rizqi Bachtiar (Universitas Airlangga, 2020)
Information and Communications Technology (ICT) has become one of the influential instruments for poverty alleviation. The argument is based on the fact that currently technology has played an important role in relation to the lives of many people. There are several projects conducted by the government in Indonesia utilising ICT to reduce poverty rate, such as establishing telecenter in some remote areas. This paper aims to identify the extent and the impact of the ICT convergence process that is carried out as an effort to improve the welfare of the community, specifically at Gubugklakah village, Malang Regency. The village is chosen as the locus of the research because the area, which is relatively far from the city center, received telecentre procurement assistance by the central government. By using descriptive qualitative methods, this study finds that ICT has not been converged to the maximum and the impact is less than optimal. Internet connection is only limited to middle and upper economic groups. The use of the world-wide-web at the village has also experienced ups and downs. For example, there is an improvement in the utilisation of techonolgy in education, tourism and government sectors which impact on a more effective work culture. People also usually surf the internet to search and watch educational, entertainment or trading content. However, the connection has a slow network connection which is problematic when many people use it. Furthermore, there is a need for educating people as well as incremental approach so that the internet can be in line with local culture.Teknologi Informasi dan Komunikasi (TIK) telah menjadi salah satu instrumen yang berpengaruh dalam pengentasan kemiskinan. Argumen tersebut didasarkan pada kenyataan bahwa saat ini teknologi telah memainkan peran penting dalam kaitannya dengan kehidupan banyak orang. Ada beberapa proyek yang dilakukan pemerintah di Indonesia yang memanfaatkan TIK untuk mengurangi angka kemiskinan, seperti membangun telecenter di beberapa daerah terpencil. Tulisan ini bertujuan untuk mengetahui sejauh mana dan dampak dari proses konvergensi TIK yang dilakukan sebagai upaya peningkatan kesejahteraan masyarakat khususnya di Desa Gubugklakah Kabupaten Malang. Desa ini dipilih sebagai lokus penelitian karena wilayah yang relatif jauh dari pusat kota mendapat bantuan pengadaan telecentre oleh pemerintah pusat. Dengan menggunakan metode deskriptif kualitatif, penelitian ini menemukan bahwa TIK belum terkonvergensi secara maksimal dan dampaknya kurang optimal. Koneksi internet hanya terbatas pada kelompok ekonomi menengah ke atas. Penggunaan world wide web di desa juga mengalami pasang surut. Misalnya, peningkatan pemanfaatan teknologi di bidang pendidikan, pariwisata dan pemerintahan yang berdampak pada budaya kerja yang lebih efektif. Orang juga biasanya menjelajahi internet untuk mencari dan menonton konten pendidikan, hiburan, atau perdagangan. Namun, koneksi tersebut memiliki koneksi jaringan yang lambat yang menjadi masalah ketika banyak orang yang menggunakannya. Selain itu, perlu adanya edukasi kepada masyarakat serta pendekatan incremental agar internet dapat sejalan dengan budaya lokal.